2019
DOI: 10.3140/bull.geosci.1747
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of coral-microbialite reefs along the French Jura platform during the Bimammatum Zone (Oxfordian, Late Jurassic)

Abstract: In the Late Jurassic, carbonate platforms and reefs were widespread in the various known geographical realms, north Tethysian, south Tethysian, north Atlantic, and Pacific (Leinfelder 2001). The many studies conducted by R. Leinfelderʼs German team during the 1990s have shown that these reefs were diversified and occupied specific ecological niches: stromatolites near the shore line, coral reefs in relatively shallow and proximal zones, siliceous sponge bioherms in deeper and distal parts of the platform, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…On the western margin of the Iberian Basin during the Kimmeridgian (Aurell et al 2003;Alnazghah et al 2013), pinnacle reefs are reported in the middle ramp (San Miguel et al 2017), with similar composition but different geometry with respect to the type 2 lens-shaped build-ups of eastern Sardinia. Carbonate ramps with ooidal shoals in the inner ramp and coral-microbial reefs in middle-ramp environment are reported from the Oxfordian of the French Jura and Paris Basin (Burgundy, Armorican and Lorraine platforms), where an epicontinental sea flooded the area among scattered emerged lands (Bertling and Insalaco 1998;Lathuilière et al 2005;Olivier et al 2011;Brigaud et al 2014;Olivier 2019).…”
Section: Comparison Of Eastern Sardinia Build-ups With Coeval Reefsmentioning
confidence: 99%
“…On the western margin of the Iberian Basin during the Kimmeridgian (Aurell et al 2003;Alnazghah et al 2013), pinnacle reefs are reported in the middle ramp (San Miguel et al 2017), with similar composition but different geometry with respect to the type 2 lens-shaped build-ups of eastern Sardinia. Carbonate ramps with ooidal shoals in the inner ramp and coral-microbial reefs in middle-ramp environment are reported from the Oxfordian of the French Jura and Paris Basin (Burgundy, Armorican and Lorraine platforms), where an epicontinental sea flooded the area among scattered emerged lands (Bertling and Insalaco 1998;Lathuilière et al 2005;Olivier et al 2011;Brigaud et al 2014;Olivier 2019).…”
Section: Comparison Of Eastern Sardinia Build-ups With Coeval Reefsmentioning
confidence: 99%